Analisis Risiko Ergonomi Menggunakan Agricultural Whole-Body Assessment (AWBA) serta Prevalensi Terjadinya Musculoskeletal Disorders (MSDs) pada Petani Karet - Lina Dianati Fathimahhayati; Theresia Amelia Pawitra; Tri Budi Purnomo; Jenny Noviani (Program Studi Teknik Industri Universitas Setia Budi, 2022)
Likewise in most agricultural work, MSDs also appears in rubber farmers because it was done with an unusual posture. This study aimed to evaluate the prevalence of MSD and to analyze the ergonomic risk of rubber farmers working posture. The NBM (Nordic Body Map) method was used to measure the prevalence of MSDs and the AWBA (Agricultural Whole-Body Assessment) method was used to calculate the risk value of the farmer's work posture. Data collected by interview and direct observation to 15 rubber farmers from 4 different plantation in Perangat Selatan Village, Kutai Kartanegara, East Kalimantan. The results showed that majority of farmers had complaints of MSDs on their waist, back, right shoulder, right upper arm, right forearm and knee. AWBA results indicated that 53% working posture categorized as high risk; 40% as medium risk and 7% as safe. The safe category only occurs in sharpening knives activity, because farmers sit while doing this activity. Suggested improvements to minimize the risk of unusual postures are to provide assistive devices such as light chairs, strollers, tables to place rubber sap to be put into sacks and to improve the design of the tapping knife. The knife should have longer handle in order to minimize the bending down posture in rubber tapping activity. Keywords: AWBA, ergonomic, NBM, rubber farmers, working posture